Artikel Analisis Semiotika Roland Barthes Dalam Film "Tuhan Izinkan Aku Berdosa" - M Alparizky; Andini Nur Bahri (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This study aims to analyze the meaning of signs in the film "Tuhan Izinkan Aku Berdosa" using Roland Barthes' semiotic approach, which includes denotation, connotation, and myth. The film was chosen because it explores themes of sin, forgiveness, and the search for identity, closely linked to social and religious values in Indonesian society. A qualitative descriptive method was used, with data collected through in-depth observation of visual elements, dialogues, and symbols within the film. The analysis results reveal that the film not only portrays individual inner conflicts when facing social and religious norms but also deconstructs social constructions of morality through rich visual symbolization. At the denotative level, the film depicts the protagonist’s journey in confronting moral dilemmas. At the connotative level, the use of colors, expressions, and settings deepens the emotional nuance of the story. Meanwhile, at the myth level, the film represents ideological struggles between religious values and individual freedom. This research concludes that "Tuhan Izinkan Aku Berdosa" serves notmerely as entertainment but also as a medium of social critique, encouraging audiencesreflect deeply on the meanings of sin, forgiveness, and personal freedom within the context of society.